Technological Intensity of Government Demand and Innovation - Viktor Slavtchev; Simon Wiederhold (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2012)
Governments purchase everything from airplanes to zucchini. This paper investigates whether the technological intensity of government demand affects corporate R&Dactivities. In a quality-ladder model of endogenous growth, we show that an increase in the share of government purchases in high-tech industries increases the rewards for innovation, and stimulates private-sector R&D at the aggregate level. We test this prediction using administrative data on federal procurement performed in US states. Both panel fixed effects and instrumental variable estimations provide results in line with the model. Our findings bring public procurement within the realm of the innovation policy debate.
Keywords: E62; H57; O31; O33; O38; 330; Government demand; technological change; endogenous growth; innovation policy; Öffentliche Beschaffung; Hochtechnologiesektor; Wirkungsanalyse; Industrielle Forschung; Innovation; Neue Wachstumstheorie; Theorie; Schätzung; USA